2016
DOI: 10.1016/j.envint.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A crossover–crossback prospective study of dibutyl-phthalate exposure from mesalamine medications and semen quality in men with inflammatory bowel disease

Abstract: Background Phthalates are widely used chemicals with ubiquitous exposure. Dibutyl-phthalate (DBP), a male reproductive toxicant in animals, is understudied in humans. Some mesalamine medications used to treat inflammatory bowel disease (IBD) have DBP in their coating, whereas other mesalamine formulations do not. Objectives Taking advantage of differences in mesalamine formulations, we investigated whether high-DBP exposure from mesalamine medications was associated with decreased semen parameters. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 72 publications
4
38
0
Order By: Relevance
“…Skakkebaek et al [82] has postulated the theory that the rising incidence of testicular cancer, cryptorchidism, hypospadias, and male infertility have all been linked to male in utero exposure to environmental endocrine disrupting chemicals (EDCs). Chemicals such as bisphenol A and phthalate, which are widespread in the environment and feature in many household items, have been shown to induce reproductive abnormalities in animal studies [83]; however, these have also been associated with abnormal semen parameters [84,85] and sexual dysfunction [86] in humans. Similarly, there is evidence that EDCs may play a role in the development of cancer [87] and MetS [88].…”
Section: Male Cancers Survivorship and Sexual And Reproductive Healthmentioning
confidence: 99%
“…Skakkebaek et al [82] has postulated the theory that the rising incidence of testicular cancer, cryptorchidism, hypospadias, and male infertility have all been linked to male in utero exposure to environmental endocrine disrupting chemicals (EDCs). Chemicals such as bisphenol A and phthalate, which are widespread in the environment and feature in many household items, have been shown to induce reproductive abnormalities in animal studies [83]; however, these have also been associated with abnormal semen parameters [84,85] and sexual dysfunction [86] in humans. Similarly, there is evidence that EDCs may play a role in the development of cancer [87] and MetS [88].…”
Section: Male Cancers Survivorship and Sexual And Reproductive Healthmentioning
confidence: 99%
“…Phthalates having a smaller molecular structure and lower molecular weight are more soluble in water and are therefore used as industrial solvents, in the composition of cosmetics and pharmaceuticals, or as insecticides; this is the case, for example, of diethyl phthalate (DEP) and di- n -butyl phthalate (DnBP) [ 2 , 3 ]. In particular, DEP is the phthalate of choice used in the cosmetic and personal hygiene products industry, both for adults and for children/infants [ 4 ], while DnBP is usually used as excipient in pharmaceuticals products [ 5 , 6 ], and it was present in cosmetics, particularly nail care products for adults [ 7 ]; in Europe this last use is forbidden by the EU cosmetics directive, Dir. 76/768/EEC, where other forbidden phthalates were also listed: di(2-ethylhexyl)-phthalate (DEHP), benzylbutylphthalate (BBP), bis2-methoxyethylphthalate, n -pentylisopentyl-phthalate, di- n -pentylphthalate, diisopentylphthalate and di ( n -butyl) phthalate (DnBP).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown significant impacts on laboratory animals but due to inadequate data, the human health impacts from low dose exposure are difficult to determine [ 6 ]. Nevertheless, some studies have shown that phthalate exposure adversely affects human male reproductive development [ 7 ] and sperm quality [ 8 , 9 ], and is also associated with risk factors for cancer, asthma and allergies [ 10 ]. Phthalates have been associated with obesity [ 11 ] but their impact on overall cardiovascular health is unclear [ 12 ].…”
Section: Introductionmentioning
confidence: 99%